Playing with Numbers 2: Complementary Software to Early Math Instruction - Aragón Mendizábal, Estíbaliz L.; Ruiz Gagigas, Gonzalo; Aguilar Villagran, Manuel; Araújo Hoyos, Antonio; Navarro Guzmán, José I. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
The interest to improve math performance involves people in different areas of life therefore may be useful for the progress of society. Frequently efforts are focused in order to obtain an ideal performance in math during Primary and Secondary school. But the bases for learning are acquired earlier (Clements & Sarama, 2007). It is importantidentify and overcome difficulties to improve performance at children in kindergarten and the first school grades (Gersten, Jordan, & Light, 2005). This research attempted to link current Educational Sciences knowledge and Psychology, connecting them with educational software that can be applied in math learning difficulties during the earlier school years. Using computer as an educational tool, students make activities based on tangible situations contributing to understand the environment and allowing them to start acquisition of mathematical knowledge and building the logical and mathematical thinking on motivating and effective way.